Sociodemographic Risk Factors for Mental Health Disorders Among School Children in Umuahia, South-East Nigeria - Ikechukwu F. Ogbonna; Chizoba F. Achor; Joseph Ezeogu (International Journal of Medicine and Health Development)
Background: Mental health disorders (MHD) have continued to gain public health importance, and studies have shown a high burden in children. However, gaps concerning MHD risk factors in children exist. Objective : To determine the sociodemographic risk factors for MHD in school children. Materials and Methods: It was a cross-sectional study of 384 school children aged 2–17 years attending primary or secondary schools in Umuahia, South-East Nigeria, and enrolled through a multistage sampling method. Their sociodemographic characteristics were obtained, and MHD was determined using the Strengths and Difficulties Questionnaire. Results: Forty-five (11.7%) of the 384 children enrolled had MHD. The sociodemographic risk factors for MHD were the children’s age, sex, and socioeconomic status (SES) of their caregivers, and their caregivers’ marital status and categories (P < 0.05). Children aged 10–13 years were eight times more likely to have MHD than children in the other age groups (adjusted odds ratio [aOR] = 7.68, 95% CI = 2.43–24.26, P = 0.001); female children were three times more likely to have MHD than their male counterparts (aOR = 2.75, 95% CI = 1.20–6.27, P = 0.016), while children of the lower SES were three times more likely to have MHD compared to children from other SES (aOR = 3.27, 95% CI = 1.04–10.25, P = 0.042). Also, children residing with widowed caregivers were five times more likely to have MHD than children residing with caregivers who belonged to another marital status (aOR = 5.19, 95% CI = 1.45–18.61, P = 0.012), and those residing with non-biological caregivers were four times more likely to have MHD than those residing with biological caregivers (aOR = 3.50, 95% CI = 1.55–7.74, P = 0.002). However, children residing with married caregivers were less likely to have MHD (aOR = 0.28, 95% CI = 0.09–0.91, P = 0.033). Conclusion: The MHD burden in school children in Umuahia, South-East Nigeria is high, and the sociodemographic risk factors for MHD were their age, sex, and the SES, marital status, and categories of their caregivers.